Increase of Th17 Cell Phenotype in Kidney Transplant Recipients with Chronic Allograft Dysfunction - Chung, Byung Ha; Kim, Kyoung Woon; Kim, Bo-Mi; Doh, Kyoung Chan; Cho, Mi-La; Yang, Chul Woo (PLOS ONE, 2016)
This study was performed to determine the association of Th17 cell phenotype with chronic allograft dysfunction in kidney transplant recipients (KTRs). We compared the expression of Th17 cell phenotype in KTRs with chronic allograft dysfunction group (CAD, n = 52) with four control groups (long-term stable KTRs (LTS, n = 67), early stable KTRs (ES, n = 28), end stage renal disease (ESRD, n = 45), and healthy control (HC, n = 26). We also performed in vitro study using human proximal renal tubular epithelial cell line (HPRTEpiC) to evaluate the effect of IL-17 on human renal tubular epithelial cells. The CAD group showed increased percentage of Th17 cells out of CD4+ T cells and also increased proportion of IL-17 producing cells out of effector memory T cells or out of CCR4+CCR6+/CD4+ T cells compared to the LTS group and other control groups. Also, the serum level of IL-17, IL-33, and RAGE, and the expression of IL-1beta, RAGE, and HMGB1 mRNA showed an increase in the CAD group compared to the LTS group. In vitro study revealed that IL-17 increased production of IL-6 and IL-8 and up-regulated profibrotic gene expression such as ACTA-2 and CTGF in HPRTEpiC in a dose-dependent manner, which suggests that IL-17 has a role in the development of renal tubular cell injury. The results of our study may suggest that increase of Th17 cell phenotype could be a marker for the chronic allograft injury; hence there is a need to develop diagnostic and therapeutic tools targeting the Th17 cells pathway.